Proposed transportation rates for Nutritional Products Sdn Bhd (The Logistics Department) / Nor Izlida Idris - Idris, Nor Izlida (1991)
One out of every two business in Malaysia uses contract transporters to conduct some parts of its activities. The cost of distribution figures high especially in manufacturing company like Nestle and other related industries/companies. This thesis is aimed to provide information regarding the actual costs involved in the operation of a fleet. It focuses on fleet costs because both the fleet operators and the company who contracted out the service use costs to evaluate the effectiveness of their fleet operation. This thesis is organised to combine the concepts of cost effectiveness and system analysis into a marketing philosophy of fleet management. To practice cost effectiveness, management must concentrate its attention on those decisions that most affect fleet costs.